HUBUNGAN POLA ASUH ORANG TUA DENGAN TINGKAT PERKEMBANGAN SOSIAL ANAK USIA 4-6 TAHUN DI TK KOTA TANGERANG - Andre Wirakusuma; Nuryanti, Nuryanti; Febi Ratnasari (Nusantara Hasana Journal, 2022)
Early childhood refers to a group of children who are in the midst of a unique growth and development process. One of the elements that affect the growth and development of children is parenting or interpersonal relationships. Social agents have a significant impact on a child’s development. Family, especially parents and siblings, is very important for the process of social development. Parenting is a reflection of the quality of the relationship between children and parents. Objective: This study aims to determine the relationship between parenting and social development of children aged 4-6 in Tangerang City Kindergarten. Method : This research is quantitative with correlational type with cross sectional approach. The subjects in this study were parents at Baitul Makmur Kindergarten, RA Pelangi Nusantara and Paud Mandiri Kota Tangerang who had 100 children aged 4-6 years. The method of taking the subject in this study using total sampling. Results: From the Chi-Square test results obtained p-value 0.000 0.05 and the Pearson correlation value of 0.489 is said to be correlated or sufficiently related. So Ha is accepted and Ho is rejected. Conclusion: There is a significant relationship between parenting patterns and the level of social development of children aged 4-6 years in Tangerang City Kindergarten.